2013
DOI: 10.1016/j.jadohealth.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Previous Use of Alcohol, Cigarettes, and Marijuana and Subsequent Abuse of Prescription Opioids in Young Adults

Abstract: Purpose There has been an increase in the abuse of prescription opioids, especially in younger individuals. The current study explores the association between alcohol, cigarette, and/or marijuana use during adolescence and subsequent abuse of prescription opioids during young adulthood. Methods We used demographic/clinical data from community-dwelling individuals in the 2006–2008 National Survey on Drug Use and Health. We used logistic regression analyses, adjusted for these characteristics, to test whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 22 publications
6
67
0
1
Order By: Relevance
“…Pesce et al (2010) also found that patients with chronic pain who used cannabis were 3.7 times more likely to test positive for other illicit drugs (e.g., methamphetamines and cocaine) than were non-cannabis users (see also Manchikanti et al, 2008). Fiellin et al (2013) also presented evidence for cannabis as a possible gateway drug to the misuse of prescription opioids among both men and women 18-25 years of age.…”
mentioning
confidence: 97%
“…Pesce et al (2010) also found that patients with chronic pain who used cannabis were 3.7 times more likely to test positive for other illicit drugs (e.g., methamphetamines and cocaine) than were non-cannabis users (see also Manchikanti et al, 2008). Fiellin et al (2013) also presented evidence for cannabis as a possible gateway drug to the misuse of prescription opioids among both men and women 18-25 years of age.…”
mentioning
confidence: 97%
“…Other studies have shown that adolescent marijuana users are more likely to be addicted to other drugs after adolescence, including tobacco, alcohol, and opioid analgesics [65][66][67][68][69][70]. There also appears a positive association with psychotic symptoms or disorders like schizophrenia and marijuana use [71][72][73][74][75].…”
Section: Adolescent Usementioning
confidence: 99%
“…Scientists at NIDA have been working hard to understand marijuana's reward system. Second, credible research has shown marijuana leads to an increase in prescription drug abuse by young people, such as oxycontin [12]. We know from research [13] and accounts from heroin addicts themselves, that once hooked on oxycontin, kids will resort to less expensive heroin to achieve their opiate high.…”
Section: Marijuana Opiates and The Gateway Effectmentioning
confidence: 99%
“…Most critical, emerging adults with heavy use backgrounds show size effects in brain areas that are involved in cognition, such as the prefrontal cortex and parietal region [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Marijuana Use Modifies Brain Structure and Physiologymentioning
confidence: 99%